PENGARUH STRUKTUR MODAL, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN : Studi Kasus Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia (BEI) - Martilova, Novera (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
The background in this study is that there is an inconsistent relationship between capital structure and firm value, profitability and firm value and firm size and firm value. The phenomenon that occurs is very interesting for further research, because it is not in line with the conditions that should occur, namely when the capital structure, profitability, and company size increase, it will result in the company's value also increasing. This research aims to examine the Effect of Capital Structure, Profitability and Company Size on Firm Value in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period. Based on the results of the research and discussion that has been carried out, it can be concluded that the research results show that the capital structure variable does not have a significant positive effect on company value in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2015-2019 period. The research results show that the profitability variable has no significant effect positively on company value in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2015-2019 period. The test results for the coefficient of determination show that the value of R Square is 0.044. This shows that the value of capital structure, profitability and firm size in the regression model is 4.4%. So the influence contribution or proportion of the independent variable is 4.4%, this explains that the independent variable has a weak influence, while the remaining 95.6% is influenced by other factors not examined in this research.